Reimagining Indonesia's Culinary Tourism: The Power of Gastronomy and Branding - Untari, Dhian Tyas; Satria, Budi (Greenation International Journal of Tourism and Management, 2023)
Indonesia, with its rich cultural heritage and diverse culinary traditions, offers a unique opportunity for the development of culinary tourism. The integration of gastronomy and branding plays a pivotal role in enhancing Indonesia’s appeal as a prime destination for food enthusiasts. This paper explores the synergy between gastronomy and tourism branding in Indonesia, emphasizing how culinary experiences can be marketed to attract both domestic and international tourists. By focusing on the authenticity, variety, and distinctiveness of Indonesian food, tourism stakeholders can craft compelling narratives that highlight the country's diverse culinary offerings. The study also examines successful branding strategies implemented in other countries, which Indonesia can adapt to position itself as a global culinary hub. Additionally, the role of local communities, chefs, and food producers in preserving traditional flavors and cooking techniques is discussed as a crucial element in building a strong culinary identity. Through effective branding, Indonesia’s culinary tourism can not only increase the country's tourism revenue but also promote sustainable practices that benefit local economies and cultures. The findings suggest that Indonesia has the potential to become a leading culinary destination, provided there is a strategic, well-coordinated effort to combine gastronomy with tourism branding.